Small‐Group Dynamics, Ideology, and Decision Making on the US Courts of Appeals. (27th December 2016) - Miller, Banks; Curry, Brett
Abstract : There is some evidence that judges who specialize in particular legal areas vote in more ideologically consistent ways than do nonspecialists. Upon replicating those individual results across multiple legal areas in the US courts of appeals, we assess how this increasing reliance on ideology by specialists affects decision making by others on a three‐judge panel. We find that judges who serve with a specialist are especially likely to vote in a manner consistent with the ideological position of the specialist with whom they serve. These results suggest that specialization has the potential to facilitate panel effects across numerous legal policy areas.